Rezension von: Taddey, Gerhard, Michael Hospin - Wunder, Gerd (Württembergisch Franken, 1982)
Gerhard Taddey: Michael Hospin. Korrekturen an einer Biographie. In: Zeitschrift f. württ. Landesgesch. 38 (1979). S. 140-163.